Role of caveolae in smooth muscle cells-mediated enhanced vasoconstriction of interlobar renal artery to angiotensin Ⅱ in SHR rats - ZHANG Hai-jun; ZHANG Xi; XIE Xiao-ping; CHANG Yao-ming; BAO Jun-xiang (Linchuang shenzangbing zazhi)
Objective To investigate the role of caveolae in higher vasoconstriction of interlobar renal artery(IRA) of spontaneously hypertensive rat(SHR) to angiotensin Ⅱ(Ang Ⅱ).Methods Isometric force recording system was used to detect the vascular function.Methyl-beta-cyclodextrin(MCD) was employed to reduce the caveolae abundance.Real-time polymerase chain reaction(RTPCR) and Western blotting were conducted to examine the expression of mRNA and protein of angiotensin type 1 receptor(AT1R).Immumoprecipitation followed by Western blotting was carried out to test the binding of caveolin-1 and AT1 R.Results As compared to Wistar Kyoto(WKY) rats,the constriction of IRA to Ang Ⅱ was increased by 32.7%in SHR(P<0.05).Meanwhile,the abundance of caveolae on vascular smooth muscle cells(VSMCs) was enhanced significantly(P<0.05).After reducing the caveolae by MCD,the intensity and sensitivity of vasoconstriction to Ang Ⅱ in IRA of SHR were partly and entirely reversed,respectively.Moreover,AT1 R protein expression was higher in IRA of SHR group than in WKY group in which the AT1 R protein expression was lowered in part by MCD incubation.In IRA of both WKY group and SHR group,Ang Ⅱ could promote the binding of AT1 R to caveolin-1(P<0.05),which was by a larger extent in SHR group than in WKY group(P<0.05).After treatment with MCD,the binding of the two proteins in IRA of SHR group was restored to the level of WKY rats.Conclusions Caveolae regulates the enhanced intensity and sensitivity of vasoconstriction to Ang Ⅱ in IRA of SHR by raising AT1 R protein content and binding of AT1 R to caveolin-1.